Anopheles coluzzii and Anopheles amharicus, new members of the Anopheles gambiae complex - Coetzee, Maureen; Hunt, Richard H.; Wilkerson, Richard; Torre, Alessandra Della; Coulibaly, Mamadou B.; Besansky, Nora J. (Zootaxa, 2013)
Two new species within the Anopheles gambiae complex are here described and named. Based on molecular and bionomical evidence, the An. gambiae molecular "M form" is named Anopheles coluzzii Coetzee & Wilkerson sp. n., while the "S form" retains the nominotypical name Anopheles gambiae Giles. Anopheles quadriannulatus is retained for the southern African populations of this species, while the Ethiopian species is named Anopheles amharicus Hunt, Wilkerson & Coetzee sp. n., based on chromosomal, cross-mating and molecular evidence.